The Importance of Vednaadhyaya in Clinical Diagnosis of Childhood Diseases - Dattatrya G. Parde,; Sadhana D. Avhale, (International Journal of Ayurveda and Pharma Research, 2022)
The knowledge of Ayurveda have been divided in eight branches i.e., Ashtangayurveda. Out of which Kaumarbhritya is the branch of Ayurveda, which deals with the knowledge of diseases and care of child right from conception till adolescence. Kashyap Samhita is the most important and main classical text of the Kaumarbhritya. The Kashyap Samhita is divided in various sections (Sthana) of which Vedanadhyaya is 25th Chapter of Sutrasthana where the symptomology of various diseases in children’s are explained and it helps in pediatric examination and diagnosis as children are not capable to speak about their symptoms themselves. The present review article is the humble effort to investigate the classical text of the Vedanadhyaya and its modern aspects. It is observable that Acharya Kashyap has integrated a broad collection of diseases of different system like skin, ENT, gastro-biliary, hematology and urinary system and has also included the Balgrahas. The symptoms described are truthful and rational in modern logical era also. Therefore, a comprehensive study of Vedanadhyaya is necessary for appropriate understanding of Ayurvedic point of view for pediatric diseases and their ordinary discriminative symptoms. It reinforces the view, that children are not miniature adults and diseases in pediatric age group have different features and requires understanding of it. This review article highlights the importance of Vednaadhyaya in clinical diagnosis of childhood diseases.